Measuring Collateral Consequences Among Individuals Registered for a Sexual Offense: Development of the Sexual Offender Collateral Consequences Measure. (April 2022) - Hamilton, Emma; Sanchez, Delida; Ferrara, Matthew L.
Collateral consequences faced by individuals convicted of a sexual offense have been widely referenced in the literature. There is yet to be a systematic examination of collateral consequences affecting individuals, however, due to measurement inconsistencies and the absence of a psychometrically validated instrument. The current study developed and validated a measure of collateral consequences faced by individuals convicted of a sexual offense. Specifically, this study investigated (a) the underlying factor structure of collateral consequences commonly endorsed by individuals convicted of a sexual offense through Exploratory Factor Analysis (EFA) procedures and (b) reliability and validity indicators of the aforementioned scale. Participants were 218 individuals convicted of and registered for a sexual offense in the state of Texas. Study measures included a pool of 66 collateral consequences items in addition to psychological self-report instruments addressing hopelessness, shame, social well-being, and discrimination. EFA results revealed a two-dimensional construct representing collateral consequences affecting areas of social and psychological well-being. The current measure demonstrated adequate reliability and validity. Limitations and future directions of findings are addressed.